Cryptogenic fibrosing alveolitis and lung cancer: the BTS study. Issue 1 (8th December 2009) - Harris, J M; Johnston, I D A; Rudd, R; Taylor, A J Newman; Cullinan, P
Abstract : Background: The risk of lung cancer is often reported to be increased for patients with cryptogenic fibrosing alveolitis (CFA). Methods: Vital status was sought for all 588 members of the British Thoracic Society (BTS) cryptogenic fibrosing alveolitis (CFA) study 11 years after entry to the cohort. Observed deaths due to lung cancer were compared with expected deaths using age-, sex- and period-adjusted national rates. The roles of reported asbestos exposure and smoking were also investigated. Results: 488 cohort members (83%) had died; 46 (9%) were certified to lung cancer (ICD9 162). The standardised mortality ratio (SMR) was 7.4 (95% CI 5.4 to 9.9). Stratified analysis showed increased lung cancer mortality among younger subjects, men and ever smokers. Using an independent expert panel, 25 cohort members (4%) were considered to have at least moderate exposure to asbestos; the risk of lung cancer was increased for these subjects (SMR 13.1 (95% CI 3.6 to 33.6)) vs 7.2 (95% CI 5.2 to 9.7) for those with less or no asbestos exposure). Ever smoking was reported by 448 (73%) of the cohort and was considerably higher in men than in women (92% vs 49%; p<0.001). Most persons who died from lung cancer were male (87%), and all but two (96%) had ever smoked. Ever smokers presented at a younger age (mean 67 vs 70 years; p<0.001) and with less breathlessness (12% smokers reported no breathlessness vs 5% never smokers; p = 0.02). Conclusions: These findings confirm an association between CFA and lung cancer although this relationship may not be causal. The high rate of smoking and evidence that smokers present for medical attention earlier than non-smokers suggest that smoking could be confounding this association.